If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 2(-4 + 0.5) = 1 Combine like terms: -4 + 0.5 = -3.5 3x + 2(-3.5) = 1 Multiply 2 * -3.5 3x + -7 = 1 Reorder the terms: -7 + 3x = 1 Solving -7 + 3x = 1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 3x = 1 + 7 Combine like terms: -7 + 7 = 0 0 + 3x = 1 + 7 3x = 1 + 7 Combine like terms: 1 + 7 = 8 3x = 8 Divide each side by '3'. x = 2.666666667 Simplifying x = 2.666666667
| X^3+279=0 | | 6x=100+2x | | 12x+5=23x | | -221+12x=23x+230 | | -5(a+1)=49(a+10) | | 9x-20=28+x | | 14p+21-8=14p+13 | | 180=90+4x+2x | | 11x-159=x+331 | | y-4=2(x-6) | | 5=-12+n | | 21x-27=22x+29 | | 3(2x+5)-x=2x+15 | | 3=6p-21 | | -317+14x=147-2x | | 12=k-5 | | 15=r+5 | | 6u=-48 | | -(-3-2x)-5= | | -35-14x=21-16x | | 10x^2-16x-6=0 | | 5x+17y=91 | | (-2i)(-8i)(2)= | | 4-6x=x+11 | | -56+24=22x+22 | | 15=2(5m+10)+3(5-4m) | | n-17=-18 | | -10(-9+x)=190 | | -116-14=-7x+213 | | (2x^2)-7y^2=-13 | | 5(5n+9)+2= | | b+42=19 |